The autologous hematopoietic stem cell transplantation in adult patients with lymphoma: Turkish Bone Marrow Transplantation Registry results - (:unkn) unknown (My University, 2007)
Turkish Bone Marrow Transplantation Registry (TBMTR) was established in 1995. Since 1992, data of adult lymphoma patients from fifteen national transplantation centers were collected and analyzed by TBMTR. A total of 437 adult lymphoma patients (185 Hodgkin's and 252 non-Hodgkin's lymphoma) undergoing autologous hematopoietic stem cell transplantation (HSCT) were registered in TBMTR from 1992 to 2002. Peripheral blood as stem cell source was used in 94% of the transplantations. Non-TBI (total body irradiation) conditioning regimens were administered in 88% of the cases. The 100-day transplantation-related mortality (TRM) was 11% in relapsed and 11% in primary refractory Hodgkin's lymphoma patients whilst TRM was found to be 9% and 30% in non-Hodgkin's lymphoma patients in first remission and in primary refractory cases, respectively. Infection was the most common cause of TRM. 10-year and 5-year survival rates were 50% and 49% in relapsed cases and primary refractory cases with Hodgkin's lymphoma, respectively; while in non-Hodgkin's lymphoma patients 10-year survival rate was 65% in cases in first remission, 7-year survival rate was 50% in sensitive relapse, 2-year survival rate was 0% in resistant relapse and 3-year survival was 24% in primary refractory cases. In conclusion, TBMTR results are comparable to EBMT and IBMTR results. Therefore, autologous HSCT may provide long-term survival in patients with Hodgkin's lymphoma as well as in patients with non-Hodgkin lymphoma in first remission and in sensitive relapse.
Keywords: Autologous stem cell transplantation; Lymphoma; Registry; Turkish Oncology Group